Energy and nutrient intake increased by 47–67% when amylase was added to fortified blended foods—a study among 12‐ to 35‐month‐old Burkinabe children. Issue 1 (3rd May 2017) - Kampstra, Nynke A.; Van Hoan, Nguyen; Koenders, Damiet J.P.C.; Schoop, Rotraut; Broersen, Britt C.; Mouquet‐Rivier, Claire; Traoré, Tahirou; Bruins, Maaike J.; de Pee, Saskia
Abstract: Adding amylase to fortified blended foods can improve energy density, and increase child's energy and nutrient intake. The efficacy of this strategy is unknown for the World Food Programme's Super Cereal Plus (SC+) and Super Cereal (SC) blends. The primary goal of this study was to investigate the increased energy intake from amylase‐containing SC+ and SC compared to control porridges in Burkinabe children. Secondly, energy intake from amylase‐containing porridges compared to CERELAC ®, Vitazom, and eeZeeBAR™ was studied. Thirdly, caregivers' ( n  = 100) porridge acceptability was investigated. The design was a randomized double‐blind controlled cross‐over trial studying the effect of amylase addition to SC+ and SC flours on porridge energy and nutrient intake in healthy Burkinabe children aged 12–23 ( n  = 80) and 24–35 months ( n  = 40). Amylase added to porridges increased energy density from 0.68 to 1.16 kcal/g for SC+ and from 0.66 to 1.03 kcal/g for SC porridges. Among children aged 12–23 months, mean energy intake from all porridges with amylase (135–164 kcal/meal) was significantly higher compared to control SC+ porridges (84–98 kcal/meal; model‐based average). Among children aged 24–35 months, mean energy intakes were also significantly higher from all porridges with amylase added (245–288 kcal/meal) compared to control SC porridges (175–183 kcal/meal). Acceptability of the porridges among caregivers was rated neutral to good, both for amylase‐added and non‐amylase‐containing porridges. These findings suggest that, among 12–35‐month‐old, adding amylase to fortified blended foods significantly increased energy and consequently nutrient intake per meal by 67% for SC+ and 47% for SC. Moreover, amylase‐containing porridges were well accepted by the caregivers.